Incidence of type 1 diabetes in children and adolescents during the COVID-19 pandemic in Germany: results from the DPV registry - Kamrath, Clemens; Rosenbauer, Joachim; Eckert, Alexander J.; Siedler, Kai; Bartelt, Heike; Klose, Daniela; Sindichakis, Marina; Herrlinger, Silke; Lahn, Valentina; Holl, Reinhard W. (Diabetes care, 2022)
The aim of this study was to investigate the incidence of type 1 diabetes in children and adolescents during the coronavirus disease 2019 (COVID-19) pandemic in Germany compared with previous years.Based on data from the multicenter German Diabetes Prospective Follow-up Registry, we analyzed the incidence of type 1 diabetes per 100,000 patient-years in children and adolescents from 1 January 2020 through 30 June 2021. Using Poisson regression models, expected incidences for 2020/21 were estimated based on the data from 2011 to 2019 and compared with observed incidences in 2020/21 by estimating incidence rate ratios (IRRs) with 95% CIs.From 1 January 2020 to 30 June 2021, 5,162 children and adolescents with new-onset type 1 diabetes in Germany were registered. The observed incidence in 2020/21 was significantly higher than the expected incidence (24.4 [95% CI 23.6-25.2] vs. 21.2 [20.5-21.9]; IRR 1.15 [1.10-1.20]; P < 0.001). IRRs were significantly elevated in June 2020 (IRR 1.43 [1.07-1.90]; P = 0.003), July 2020 (IRR 1.48 [1.12-1.96]; P < 0.001), March 2021 (IRR 1.29 [1.01-1.65]; P = 0.028), and June 2021 (IRR 1.39 [1.04-1.85]; P = 0.010).A significant increase in the incidence of type 1 diabetes in children was observed during the COVID-19 pandemic, with a delay in the peak incidence of type 1 diabetes by ∼3 months after the peak COVID-19 incidence and also after pandemic containment measures. The underlying causes are yet unknown. However, indirect rather than direct effects of the pandemic are more likely to be the cause.